PERTANGUNGG JAWABAN NOTARIS PPAT DALAM MELAKUKAN PELAYANAN PEMBAYARAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) - Leomuwafiq, Ghazi (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
Notary Services as a part of the service to the community, should walk parallel to the development of society in the present and future. One of notary services conducted in his position as PPAT is Payment service for land and building Rights (BPHTB) in terms of buying and selling of land rights. BPHTB payment is one of the conditions for the registration of land rights transitional in the provisions of Article 103 of the regulation of the Minister of Agrarian state/head of National Land Agency number 3 year 1997.  Due to the existence of the BPHTB payment obligation resulted in the time period between the purchase and sale agreement carried out in front of the notary, with the implementation of the sale/turnover of land rights carried out in front of the authorized PPAT has a distance For a relatively long period of time, and usually buyers who conduct buy and sell rights to the land have handed over a certain amount of money for the cost of BPHTB by giving it to the notary public that makes the transitional deed. On the one hand, due to the relatively long period between the trade and Sale Alliance carried out before the notary with the sale and purchase carried out in the presence of the authorized PPAT, while the cost of BPHTB is deposited by the client to the notary public as the official The makers of Land deed (PPAT), allowing the opportunity of misappropriation by means of unpaying or embezzlement of BPHTB funds deposited